Peran Restoran Garuda Dalam Mendukung Wisata Kuliner Halal di Kota Medan (Studi Kasus : Restoran Garuda Jl. H. Adam Malik No. 14 Medan) - Chair, Marsari; Yusrizal, Yusrizal; Nasution, Juliana (Universitas Labuhanbatu, 2023)
Looking for a halal restaurant or restaurant is a must for Muslim visitors, because one proof of obedience to Allah's commands is to eat halal food and not eat unclean food. The large number of restaurants or restaurants in Medan that provide non-halal food makes Muslim tourists or Muslim visitors confused about choosing a halal restaurant. Finding halal food in the city of Medan is not difficult, because the ethnic population of Medan is Malay, most of the Malays are Muslims. One of the restaurants in Medan with the characteristics of Minang-Malay cuisine is